What do young Australian adults know about modifiable risk factors for dementia? - Hannah A. D. Keage (BMC, 2021)
Abstract Background There are well established modifiable risk factors for late-life dementia. These risk factors account for over 30% of population attributable dementia risk and accrue over the lifespan. Young adults have the greatest potential to reduce their own risk for dementia. This study aimed to investigate what young Australian adults know about dementia and its risk factors, and further, how they estimated these risks. Methods An online survey promoted through various social media platforms was completed by 604 young Australian adults aged 18–44 years of age. Results Seventy percent of participants had a limited understanding of dementia (identifying cognitive or functional impairment), 25% had a good understanding, with 5% having no understanding. Twenty percent of respondents thought there were no modifiable risk factors for dementia. Less the half of participants agreed with two of the nine established dementia risk factors (hearing loss in midlife and education in early life), with over half of participants agreeing to the remaining seven risk factors. Females consistently judged the risks conferred by the nine established dementia risk factors to be higher than males. Those who were lonely judged the dementia risk conferred by loneliness to be higher than those who were not lonely; and smokers judged the dementia risk conferred by smoking to be less than non-smokers. Conclusion Young adults have the greatest potential to change their dementia risk, and these findings show that there are important gaps in knowledge of dementia and its risk factors in this group.